MOTIVATIONAL MECHANISM OF ENTERPRISE PERSONNEL MANAGEMENT AS A MEANS OF ENSURING PERSONNEL SECURITY - DIACHKOV, Dmytro; POTAPIUK, Iryna; KAPKO, Viacheslav; TRONEVSKYI, Vitalii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The scientific article is devoted to considering the importance and peculiarities of forming the motivational mechanism of enterprise personnel management as a means of ensuring personnel security.The author emphasizes that staff motivation is a key factor for effective management, involvement of employees in the performance of tasks, achievement of the organization’s mission, increase of labour productivity, reduction of staff turnover, and strengthening of the company's competitiveness. It combines art, creativity, and a deep understanding of the psychology of employees' needs and motives, encouraging them to engage in activities that meet the goals, interests, and strategy of the organization and the manager.It is noted that the motivational mechanism, the careful formation of which is a necessity for every enterprise, acts as a tool to ensure the interest of employees in achieving economic and social results. In this process, labour productivity plays a vital role as a key indicator of labour activity. It is most strongly influenced by factors such as salary, working conditions, and work content. These aspects are directly related to the motivational sphere of employees, contributing to their efficiency and effectiveness.The effective use of motivational mechanisms in human resources management to ensure personnel security can solve several essential problems. This includes identifying and preventing employee threats, such as fraud, disclosure of trade secrets, collusion with competitors, or deterioration of the psychological climate in the team. The motivational mechanism can also monitor employees, especially in critical commercial projects, and conduct internal investigations in controversial or risky situations.
Keywords: enterprise; personnel security; motivation; personnel management; motivational mechanism